The Influence Of OHS Internal Communication On The Level Of Compliance In The Use Of Personal Protective Equipment (PPE) For Workers At Trisula Callender Hamilton Bridge Project - Checi Arum Septiani; Riza Yuliawati (Journal for Quality in Public Health, 2025)
One of the causes of work accidents is non-compliance with the use of PPE (Personal Protective Equipment). Occupational Health and Safety (OHS) communication is one of the company's efforts to improve the safety and health performance of workers. Based on field observations, internal OHS communication has been implemented in the company. However, it is known that there are still many workers who do not behave safely when using PPE. Furthermore, 83% of the observed workers did not comply with the standards for using PPE. This figure indicates that the level of worker compliance with PPE use is still significantly lacking for safe work and, if left unchecked, can have fatal consequences. Thus, research is needed to explore the influence of providing internal OHS communication on workers' compliance with PPE use. This quantitative research used a cross-sectional observation method. The research findings show that there is no influence between internal OHS communication and the level of worker compliance with PPE use, where the P-value is >α (0.890>0.05). Data were collected using a questionnaire distributed to workers and staff, with a total of 44 respondents. Logistic regression was used for data analysis in this study. The aim of this research is to determine the effect of implementing internal OHS communication on the level of worker compliance with PPE use.